The Statistical Measurement of the "Velocity of Circulation of Goods" - Marget, A. W. (Quarterly Journal of Economics, 1932)
The notion of a “velocity of circulation of goods” and the desirability of measuring it statistically, 1.— The problem is identical with that of obtaining a statistical measure of the ratio of the physical volume of sales of goods to the physical volume of goods intended for sale, 6. — The “physical volume of sales of goods” and its possible substitutes, 6. — The “physical volume of goods intended for sale,” and its various components, 21.— The possibility of using figures for “stocks” of commodities on hand as indicators of movements in the “velocity of circulation of goods,” 29.— The great differences of opinion which exist with respect to the extent and the nature of the variations in the “velocity of circulation of goods” make the statistical measurement of this velocity imperative, 33.